Рівень життя працівників важкої промисловості України у 1944–1956 рр. - Татарінов, І. (Український історичний збірник, 2010)
Basing on little-known archival and printed sources the author investigates material conditions of life and lights up daily life of heavy-industry workers in hard conditions of post Second World War реriod. In the article also is analyzing the level and quality of life of Ukrainian workers.